Neurological Manifestations In Type- 1 Diabetes Mellitus In Children - Al-Naddawi, Mahjoob N.; Al-janabi, Muhi K.; Al-kafaji, Hamid B. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: Diabetes mellitus type-1 is the most common endocrine metabolic disorder in childhood. Mononeuropathy, generalized polyneuro-pathy and autonomic neuropathy are frequent complications of diabetes mellitus and may give rise to troublesome manifestations.Methods: sixty children suffering from type 1 diabetes mellitus admitted in Children Welfare Hospital- Medical City-Baghdad in the period from 1st Dec2000-31stJuly 2001 were included inthis prospective descriptive study. History, especially symptoms of peripheral neuropathy, examination specially signs of peripheral neuropathy, absent sinus arrhythmia and posturalhypotension and investigations like nerve conduction study were all performed and analyzed.Results:The study showed that out of 60 diabetic children 26(43.3%) had symptomatic polyneuropathy, 18 (30%) had postural hypotension and 16 (26.6%) had absent sinus arrhythmia. Neurological manifestations of diabetes mellitus occur frequently in diabetic children with long duration of illness.Polyneuropathy is sensory more than motor and affected the lower limbs more than the upper limbs.Conclusion: Early diagnosis of autonomic neuropathy in diabetic children is simple easy and requires minimum cooperation, so as detection of peripheral neuropathy in asymptomatic by nerve conduction study.